Comparison of analytical models for Ground Heat Exchangers - Christodoulides, Paul; Skaliontas, Andreas; Aresti, Lazaros; Florides, Georgios A. (My University, 2024)
GSHP systems, a form of shallow geothermal energy system, are used for heating and cooling usuing Ground Heat Exchangers (GHEs) that extract/reject heat from/to the ground. In such systems, the thermal response is represented by the temperature change within the GHE and the surrounding earth as a function of heat extraction or injection. There exist several mathematical models, both analytical and numerical, in the literature that govern the thermal response of GHEs. All such models are based on Fourier’s law, which allows the determination of heat flow due to conduction. Regarding numerical models, they are obviously more accurate than analytical models and can represent the GHE in greater detail. However, numerical models may be too time-consuming for building energy simulations and consequently of limited use in practical applications. In such case analytical models can play a crucial role. Analytical models can be used as alternatives to one another, depending on the case and the accuracy required to solve a problem. Some of these will be applied to an existing case study of a vertical GHE in the Mediterranean island of Cyprus and be compared to the experimental data and conclusions will be derived regarding the accuracy and suitability of each.
Keywords: GHE analytical models; GHE analytical models comparison; Ground Heat Exchanger